1993
DOI: 10.1002/bjs.1800800342
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of macrophage function by suture materials and anastomotic recurrence of Crohn's disease

Abstract: After surgical excision of bowel, Crohn's disease is likely to recur around the anastomosis. It is suggested that this may indicate a biological effect of suture materials on gastrointestinal immunology. To investigate this, the influence of six suture materials on the function of macrophages obtained from the rat peritoneal cavity and human intestinal mucosa was assessed. All materials significantly impaired macrophage function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Concern has been raised that anastomotic stapling techniques result in a localized ischemic injury that might increase CD recurrence 23,54. Conversely, suture materials have been found to alter macrophage function, and this has been proposed as a reason why hand‐sewn anastomoses might be at higher risk 55. Clinical studies have had variable results.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Concern has been raised that anastomotic stapling techniques result in a localized ischemic injury that might increase CD recurrence 23,54. Conversely, suture materials have been found to alter macrophage function, and this has been proposed as a reason why hand‐sewn anastomoses might be at higher risk 55. Clinical studies have had variable results.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In five patients with CD, intestinal anastomoses were constructed with linear staplers, creating wide side-to-side anastomoses. The choice of this type of anastomosis was based on our own encouraging experience in adult patients and convincing positive data on this technique from the literature (8,9,10).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, surgical injury to the patient could be minimized and the bowel function could recover earlier. Moreover, previous studies demonstrated that persistent foreign bodies may be responsible for anastomotic recurrence of cancer and inflammatory bowel disease and affect radiological examination [17,18] . Although no recurrence at anastomotic site was found in our study during the 6-mo follow-up period, further study is needed.…”
Section: Discussionmentioning
confidence: 99%